Numerical simulation of cerebrospinal fluid hydrodynamics in the healing process of hydrocephalus patients - Gholampour, S.; Fatouraee, N.; Seddighi, A. S.; Seddighi, A. (Journal of applied mechanics and technical physics, 2017)
Three-dimensional computational models of the cerebrospinal fluid (CSF) flow and brain tissue are presented for evaluation of their hydrodynamic conditions before and after shunting for seven patients with non-communicating hydrocephalus. One healthy subject is also modeled to compare deviated patients data to normal conditions. The fluid-solid interaction simulation shows the CSF mean pressure and pressure amplitude (the superior index for evaluation of non-communicating hydrocephalus) in patients at a greater point than those in the healthy subject by 5.3 and 2 times, respectively.